Method for manufacturing a watch or jewellery part and said watch or jewellery part

By forming a stable metal oxide shell on the gold nanoparticles, ensuring color maintenance and improving mechanical properties, the problems of unstable color and insufficient mechanical properties of gold materials in the prior art are solved, and high-quality manufacturing of high-end watches or jewelry is achieved.

JP2025510689APending Publication Date: 2025-04-15PATEK PHILIPPE SA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024555966
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-06
Filing Date
2023-04-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art has the surface color of the gold material manufactured 18 carats or more remains unstable, and the mechanical properties are insufficient to meet the needs of high-end watches or jewelry.

Method used

By producing Au@ metal oxide nanoparticles, where the gold core is covered with metal oxide shell, and by specific synthesis and treatment methods, the nanoparticles remain unchanged during the manufacturing process, forming a composite material with good mechanical properties.

Benefits of technology

The color of 18 carats or more gold materials is achieved to maintain stable color, and the obtained clocks or jewelry have excellent mechanical properties such as hardness, wear resistance and toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510689000001_ABST
    Figure 2025510689000001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a watch or jewellery piece from a material containing at least 18 carat gold, the method comprising the steps of: a) producing Au@metal oxide nanoparticles, the step a) comprising at least the sub-steps a1) synthesizing gold nanoparticles having dimensions and shapes that provide a plasmonic effect, a2) mixing the gold nanoparticles from step a1) with a surfactant that includes functional groups for coupling to a metal oxide while maintaining the plasmonic effect, and a3) forming a metal oxide shell while maintaining the plasmonic effect; b) producing a semi-finished product from a material comprising at least 18 carat gold using the Au@metal oxide nanoparticles from step a) while maintaining the plasmonic effect, the semi-finished product having a color in the dry state such that the difference ΔE in the CIE Lab color space between the color of the obtained semi-finished product and the color of the Au@metal oxide nanoparticles formed in step a) is less than 10; c) producing a watch or jewellery part from said material containing at least 18 carat gold, while maintaining the plasmonic effect, using the semi-finished product obtained in step b). The present invention relates to a method comprising the steps of: The invention also relates to a watch or jewellery part obtained by the manufacturing method defined above, said watch or jewellery part having a parameter -5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a watch or jewellery part from a material containing at least 18 carat gold, i.e. at least 75% by weight of gold relative to the total weight of the material.

[0002] The invention also relates to a semi-finished product for the production of a watch or jewellery part, and to said watch or jewellery part possibly obtained by said manufacturing method. [Background technology]

[0003] Gold alloys, in the form of evaporated coatings or in solid form, are commonly used in the manufacture of watches or jewelry components. These alloys are conventionally yellow, red or grey. Gold alloys are coloured to distinguish them from the original colour of gold and can be obtained by traditional metallurgical routes or by using gold nanoparticles coated with at least one layer of a metal oxide such as silicon, zirconium or titanium oxide, based on the plasmonic effect of gold nanoparticles. The notation Au@metal oxide is used to refer to such gold nanoparticles coated with a metal oxide shell. Indeed, gold nanoparticles (typically ranging in size from 2 to 200 nm) have a plasmonic effect. The plasmonic effect consists of the oscillation of the electron cloud of the nanoparticle when the nanoparticle is exposed to an electromagnetic field. More specifically, under the influence of the oscillating electric field of light, the free electrons of the metal nanoparticle oscillate with respect to the metallic network. At certain frequencies, i.e. at certain wavelengths, these oscillations acquire large amplitudes due to a resonance phenomenon. This is called plasmonic resonance (a simplification of localized surface plasmon resonance, LSPR). The light absorption is maximum at the resonance frequency. After absorption, the surface plasmons lose energy either radiatively (light scattering) or non-radiatively (in the form of heat).

[0004] This plasmonic effect gives gold nanoparticles very attractive optical properties. The LSPR leads to a resonance in the visible range. It is therefore possible to excite gold nanoparticles with visible light and they play a major role in the color properties of the nanoparticles. The LSPR depends especially on the size and shape of the nanoparticle. For example, for nanospheres, the gold resonance is located at about 520 nm in aqueous solution and changes very little with sizes in the range of 2 to 50 nm. These nanoparticles appear ruby ​​red. However, the position of the absorption band and its width, and therefore the color, change depending on the size of the nanoparticle, and as this increases, the LSPR band moves towards longer wavelengths and broadens. The color changes not only with the size of the nanoparticle, but also with the shape of the nanoparticle, which depends on the production conditions. For elongated nanoparticles such as nanorods, the plasmonic resonance shifts to the red as the aspect ratio increases. Thus, gold nanoparticles can change color from red to purple depending on their size. Other colors, such as green and blue, can be obtained by exploiting the shape factor, with more or less elongated nanoparticles (rods).

[0005] EP 1 887 052 ​​describes pieces composed of colored ceramics, the pigment being composed, for example, of gold nanoparticles coated with crystalline silica. The pieces obtained are in the red range. The amount of pigment in the ceramic is less than 5% by weight. This document therefore does not describe any components containing at least 75% by weight of gold.

[0006] EP 2 369 022 describes a method for producing a solid material containing at least 12 or even 18 carat gold formed from gold nanoparticles coated with silica. The color of the gold nanoparticles used is adjusted according to the size, the geometric shape (spherical, cylindrical and pyramidal), the composition and the chemical environment of the nanoparticles. The solid material is obtained by sintering by heating accompanied by microwave radiation, which does not allow to change the specific coloring of the gold nanoparticles used. However, the preparation of a solution of bright red gold nanoparticles is described, the solution of gold nanoparticles coated with silica is purple and the pellets obtained after heating and microwave irradiation are black. The method described therefore does not make it possible to guarantee that the color of the nanoparticles is preserved and is therefore not robust enough.

[0007] EP 3 482 851 describes a method for producing a material containing at least 18 carat gold, formed by the aggregation of gold nanoparticles in a matrix of titanium dioxide. However, this method is complicated, since it requires the use of solvents and the heating of the mixture formed in the reactor. In addition, due to the significant absorption or non-ideal optical properties for the light transmission of titanium dioxide, the penetration depth of the light through the material is not sufficient to obtain the maximum plasmonic effect of the gold nanoparticles, and therefore the color of the material obtained is not deep black. In addition, it has been shown that the powder obtained is black before the compression and sintering steps, but following these two steps, the material is anthracite in color. Thus, the initial color of the nanoparticles changes. In addition, the mechanical properties of titanium dioxide, for example hardness, are not always sufficient to meet the specifications imposed depending on the composition.

[0008] The present invention aims to remedy these drawbacks by proposing a method for manufacturing a watch or jewellery piece from a material containing at least 18 carat gold, which makes it possible to guarantee that the colour of the nanoparticles used is preserved and stable.

[0009] Another object of the invention is to propose a method for manufacturing a watch or jewellery part, which makes it possible to obtain a composite part containing at least 18 carat gold and having very good mechanical properties.

[0010] Another object of the invention is to propose a method for manufacturing a watch or jewellery part from a material containing at least 18 carat gold, which makes it possible to obtain in a simple manner dark components, grey or black, in particular a deep black colour. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] European Patent No. 1 887 052 [Patent Document 2] European Patent No. 2 369 022 [Patent Document 3] European Patent Application Publication No. 3 482 851 Summary of the Invention

[0012] To this end, the invention relates to a method for manufacturing a watch or jewellery part from a material containing at least 18 carat gold, said method comprising the steps of: a) forming a solution of Au@metal oxide nanoparticles comprising a gold core coated with a metal oxide shell, the step a) comprising at least a1) synthesizing gold nanoparticles by reacting a gold precursor with a reducing agent, said gold nanoparticles having dimensions and shapes that provide a plasmonic effect at least in the visible range; a2) mixing the gold nanoparticles obtained in step a1) with a solution of a surfactant comprising a functional group for coupling to a metal oxide and maintaining stirring for a sufficient time such that the surfactant coats the gold nanoparticles while maintaining the plasmonic effect; a3) A sub-step of forming a metal oxide shell by reacting a metal oxide precursor with the gold nanoparticles obtained in sub-step a2) while maintaining the plasmon effect including the step of, b) A step of producing a semi-finished product from a material containing at least 18 karat gold using the solution obtained in step a) for the purpose of forming the timepiece or jewelry part while maintaining the plasmon effect, wherein the resulting semi-finished product has a color such that the difference ΔE in the CIE Lab color space between the color of the resulting semi-finished product in the dry state and the color of the Au@metal oxide nanoparticles formed in step a) is less than 10, preferably 8 or less c) A step of producing a timepiece or jewelry part from the material containing at least 18 karat gold using the semi-finished product obtained in step b) while maintaining the plasmon effect relating to a method comprising.

[0013] Accordingly, the method according to the invention makes it possible, in particular during the procurement of the semi-finished product, to keep the color of the synthesized gold nanoparticles unchanged and to obtain a component containing at least 18 karat gold having substantially the same color as the initially synthesized gold nanoparticles, which color is advantageously black.

[0014] The invention also relates to a semi-finished product from a material containing at least 18 karat gold, which is likely to be obtained during the implementation of the method for manufacturing a timepiece or jewelry part as defined above, said semi-finished product having a color defined in the CIE L*a*b color space by the parameters -5 < a* < 5, -5 < b* < 5, and L* < 15, preferably -1 < a* < 1, -1 < b* < 1, and L* < 13.

[0015] The invention also relates to a timepiece or jewelry part that is likely to be obtained by the manufacturing method as defined above, said timepiece or jewelry part being obtained using a semi-finished product having a color defined in the CIE L*a*b color space by the parameters -5 < a* < 5, -5 < b* < 5, and L* < 15.

[0016] Other characteristics and advantages of the invention will become apparent on reading the following detailed description of different embodiments of the invention, given by way of non-limiting example and with reference to the attached drawings, in which: [Brief description of the drawings]

[0017] [Figure 1] 3A-3D diagrammatically illustrate the steps of a first variant of the method according to the invention; [Diagram 2] FIG. 3 shows diagrammatically the steps of a second variant of the method according to the invention. [Diagram 3] FIG. 2 is an image obtained by transmission electron microscopy (TEM-scale 20 nm) of Au@metal oxide nanoparticles obtained according to step a) of the method according to the invention. [Figure 4] FIG. 2 shows the reflectance curve of black Au@SiO2 nanoparticles obtained according to step a) of the method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present invention relates to a method for manufacturing a watch or jewellery part from a material containing at least 18 carat gold, i.e. at least 75% by weight of gold relative to the total weight of the material.

[0019] According to the present invention, with reference to Figs. 1 and 2, the method comprises: a) forming a solution of Au@metal oxide nanoparticles comprising a gold core coated with a metal oxide shell, the step a) comprising at least a1) synthesizing gold nanoparticles in solution by reacting a gold precursor with a reducing agent, said gold nanoparticles having dimensions and shapes that give a plasmonic effect at least within the visible range corresponding to a given color X; a2) mixing the solution of gold nanoparticles obtained in step a1) with a solution of a surfactant comprising functional groups for coupling to metal oxides and maintaining stirring for a sufficient time such that the surfactant coats the gold nanoparticles while maintaining the plasmonic effect, the resulting nanoparticles having a color X1; a3) forming a metal oxide shell by reacting a metal oxide precursor with the gold nanoparticles obtained in substep a2) while maintaining the plasmonic effect, the formed Au@metal oxide nanoparticles having a color X2, measured in powder form, such that in the dry state the color difference ΔE in the CIE Lab color space between colors X1 and X2 is preferably less than 8, preferably less than 5, more preferably less than 3 or even less than 1, and the color difference ΔE in the CIE Lab color space between colors X and X2 is preferably less than 8, preferably less than 5, more preferably less than 3 or even less than 1. and b) using the solution obtained in step a) to produce a semi-finished product from a material containing at least 18 carat gold, with the purpose of forming said watch or jewellery part while maintaining the plasmonic effect, the semi-finished product obtained having a colour X3 such that the difference ΔE in the CIE Lab colour space between the colours X2 and X3 is less than 10, preferably less than 8, more preferably less than 7, and the difference ΔE in the CIE Lab colour space between the colours X and X3 is preferably less than 10, more preferably less than 8, more preferably less than 7; c) using the semi-finished product obtained in step b) to produce a watch or jewellery part from said material, comprising at least 18 carat gold, while maintaining the plasmonic effect, said watch or jewellery part obtained having a colour X4 such that the difference ΔE in the CIE Lab colour space between the colours X2 and X4 is preferably less than 10, preferably less than 8, more preferably less than 7, and the difference ΔE in the CIE Lab colour space between the colours X and X4 is preferably less than 10, more preferably less than 8, more preferably less than 7. Includes.

[0020] The color difference or color deviation ΔE in the CIE Lab color space is defined as a measure of the difference between two colors according to formula (I):

number

number

number

number

number

number

number

[0021] A color difference ΔE between two colors of less than 10, preferably 8 or less, and more preferably 7 or less indicates that the two colors are substantially identical, at least one of which is unchanged relative to the other.

[0022] The synthesis of gold nanoparticles by reducing a gold precursor is a synthesis known to the skilled person, who knows how to select different parameters such as concentrations of reagents, concentration ratios, solvents, synthesis methods with heating, reflux, etc., which are selected so as to give said gold nanoparticles at least an overall plasmonic effect within the visible range corresponding to a given color X, in order to obtain gold nanoparticles with the same or different dimensions and shapes. In fact, the color of the gold nanoparticles varies depending on the size and shape of the nanoparticles. Colors from red to purple can be obtained depending on the size, generally obtained with spherical nanoparticles, while colors such as green and blue can be obtained by taking advantage of the shape factor, taking advantage of more or less elongated nanoparticles, for example in the form of rods. It is also possible to have shapes such as cubes, stars, etc. In particular, it is possible to control the size of the particles by taking advantage of the gold / reducing agent ratio. The gold nanoparticles obtained in substep a1) preferably have dimensions less than 200 nm, preferably between 1 nm and 200 nm, more preferably between 20 nm and 200 nm. There are numerous publications on different methods for synthesizing gold nanoparticles, which make it possible to control the size and shape of said gold nanoparticles in order to obtain a given color X.

[0023] Advantageously, in substep a1), the gold precursor is a gold salt such as HAuCl4, preferably in an aqueous solution, at a concentration between 2 g / l and 10 g / l.

[0024] Advantageously, in substep a1), the reducing agent can be NaBH4 or sodium citrate, preferably in the form of an aqueous solution, at a concentration between 25 g / l and 75 g / l. Sodium citrate is preferred. Such a reducing agent has the advantage that it also has the role of a stabilizer making it possible to maintain the gold nanoparticles in solution.

[0025] Substep a1) preferably comprises mixing an aqueous solution of the gold precursor with an aqueous solution of a reducing agent at an ambient temperature of 25° C., in which the molar ratio of gold / reducing agent in the solution is between 1 / 50 and 1 / 20.

[0026] In substep a2), the surfactant used, in addition to its coupling properties with the metal oxide, is preferably a stabilizer for the gold nanoparticles prepared in substep a1). This surfactant is advantageously amphiphilic and soluble in water and organic solvents. In addition to its functional groups for coupling to the metal oxide, such as C=O groups, the surfactant contains functional groups CH2, which provide hydrophobicity, and CN groups, such as pyrrolidone groups, which give it its hydrophilic properties.

[0027] The surfactant is preferably selected from the group comprising polyvinylpyrrolidone (PVP), gelatin, silane derivatives, and silicate derivatives.

[0028] The colour X1 of the nanoparticles obtained in step a2) may be identical or different to the colour X of the nanoparticles obtained in step a1), depending on the surfactant concentration.

[0029] The gold nanoparticle / surfactant solution is continuously and vigorously stirred for preferably 6 to 12 hours, i.e., the time necessary to replace the reducing agent with the surfactant and protect the gold nanoparticles.

[0030] The surfactant is preferably polyvinylpyrrolidone (PVP). The PVP used in substep a2) advantageously has a molar mass between 5000 g / mol and 20000 g / mol and is in the form of an aqueous solution with a concentration between 1 g / l and 10 g / l.

[0031] The molar ratio of gold to PVP in the solution is preferably 1 / 1 to 3 / 1.

[0032] When the surfactant is PVP, the gold nanoparticles / PVP solution is preferably continuously and vigorously stirred for 6 to 12 hours, i.e. the time necessary to replace the citrate with PVP and to protect the gold nanoparticles. PVP is a surfactant that prevents aggregation and precipitation of the nanoparticles due to its hydrophobic alkyl functional groups and its hydrophilic pyrrolidone groups. In addition, in a manner that is particularly advantageous for the present invention, PVP has a better affinity with silica, for example, apparently due to its C=O functional groups.

[0033] The nanoparticles protected by surfactant, in particular by PVP, are then recovered for substep a3) or preferably for intermediate substep a4). Indeed, in a particularly preferred manner, step a) comprises an intermediate substep a4) between substep a2) and substep a3), which comprises the elimination of excess surfactant, in particular excess PVP. To do this, the nanoparticles obtained in substep a2) are recovered and concentrated by centrifugation before being carried out during substep a3). In a particularly advantageous manner, this centrifugation step makes it possible to wash the nanoparticles before being resuspended in alcohol, as described below. This washing makes it possible to control the thickness of the metal oxide shell, more particularly the thickness of the oxidized silica shell, in order to obtain nanoparticles with an oxide shell of uniform thickness.

[0034] According to substep a3), the metal oxide is preferably selected from the group comprising silicon oxide, zirconium oxide and titanium oxide. Silicon oxide is particularly preferred. Thus, nanoparticles are synthesized that comprise a gold core coated with a shell of silica oxide or zirconium oxide or titanium oxide. Preferably, nanoparticles are synthesized that comprise a gold core with a silica or zirconium oxide shell, more preferably nanoparticles are synthesized that comprise a gold core with a silica oxide shell.

[0035] The metal oxide precursor can be selected from the group comprising tetraethoxysilane for the silica shell, titanium butoxide for the titanium dioxide shell and zirconium butoxide for the zirconia shell. Other precursors can also be used. The silicon oxide precursor is advantageously tetraethoxysilane (TEOS) in an alcoholic solution (for example ethanol), preferably to obtain a silica shell. The reaction is based on the Stober synthesis and is catalyzed by ammonia. The gold nanoparticles protected by surfactant, in particular PVP, recovered in substep 2) or preferably in substep a4) are transferred to a solution of alcohol and ammonia as described above. An alcoholic solution of the oxide precursor is then immediately added dropwise, with vigorous stirring. The reaction is preferably stopped after 3 hours. The resulting Au@metal oxide nanoparticles are then either kept in solution and recovered for use in substep b1), as described below, or dried in powder form according to substep b4). The resulting Au@metal oxide nanoparticles can also be recovered and dried in powder form and then dissolved again for use in substep b1).

[0036] The method parameters of substep a3) are selected to form a metal oxide shell, preferably a silicon oxide shell, in which the plasmonic effect is maintained, and the formed Au@oxide nanoparticles have a color X2, measured when the Au@oxide nanoparticles are in dry, powder form. In particular, the surfactant concentration is preferably selected such that the initial color of the gold nanoparticles prepared in substep a1) is preserved, and the color difference ΔE in the CIE Lab color space between colors X and X1, X1 and X2, and X and X2 is preferably less than 8, preferably less than 5, preferably less than 3, more preferably less than 1.

[0037] In particular, the thickness of the shell can vary depending on the oxide / gold precursor ratio or the reaction time. Due to its affinity with silica, the surfactants used, in particular PVP, advantageously make it possible to obtain a uniform silica shell around the gold nanoparticles.

[0038] The thickness of the shell is preferably less than 100 nm, preferably 2 nm to 50 nm, more preferably 10 nm to 40 nm. The main thing is that the color X2 of the obtained Au@oxide nanoparticles does not change and is maintained with respect to the color X of the gold nanoparticles prepared first.

[0039] According to a particularly preferred embodiment, sub-step a1) is to prepare black X gold nanoparticles defined in the CIE L*a*b color space by parameters -5 < a* < 5, -5 < b* < 5, and 0 ≤ L* < 10, preferably -1 < a* < 1, -3 < b* < 3, and 0 ≤ L* < 6. An aqueous solution of a gold precursor, preferably HAuCl4, is mixed with an aqueous solution of sodium citrate at an ambient temperature of 25 °C, where the molar ratio of gold / sodium citrate in the solution is 1 / 50 to 1 / 20.

[0040] In a particularly advantageous manner, the reaction is carried out at ambient temperature (25 °C) without energy input. A colloidal networked nanostructured gold formed by interconnected gold crystals provides compact gold nanoparticles of different sizes from 40 nm to 200 nm and different shapes (nanospheres, clusters, etc.) of black X defined above. The frequency of photons absorbed by the black gold nanoparticles strongly depends on the shape and size of the nanoparticles due to the LSPR effect. Thus, the obtained polydisperse and polymorphic gold nanoparticles can absorb a wide range of light, thereby giving the black color defined above.

[0041] These black gold nanoparticles are then preferably prepared using PVP according to sub-steps a2) and a4). The molar ratio of gold / PVP in the solution is 1 / 1 to 3 / 1.

[0042] The darker the color of the nanoparticles is maintained as the nanoparticle solution is diluted with PVP. The more the solution is concentrated with PVP, the more PVP tends to control the shape and size of the nanoparticles by destroying the networked shape of the gold nanostructure and giving a reddish color.

[0043] The black gold nanoparticles, preferably prepared with PVP, are then used to form Au@metal oxide nanoparticles, preferably Au@silicon oxide or Au@zirconium oxide nanoparticles of color X2 according to substep a3), the PVP concentration being selected such that color X2 is preferably similar to color X, so that the black color X of the gold nanoparticles is preserved and does not change.

[0044] After preparing the solution of Au@metal oxide nanoparticles according to step a), the Au@metal oxide nanoparticles can be used in the form of a solution or dried in powder form. For this, the Au@metal oxide nanoparticles of the solution obtained in step a) are washed several times with an alcohol, such as ethanol, and then collected by centrifugation. The Au@metal oxide nanoparticles, preferably Au@silicon oxide or Au@zirconium oxide nanoparticles, are then dried, for example in an oven at 60° C., for at least 6 hours, preferably at least 12 hours.

[0045] The Au@metal oxide nanoparticles are used in solution or powder form to obtain the amount of gold required to produce a semi-finished product from a material containing at least 18 carat gold, for the purpose of forming said watch or jewelry part.

[0046] The surfactants, in particular PVP, and the appropriate metal oxide shell make it possible to maintain the plasmonic effect, and the resulting semi-finished product has a color X3 such that the difference ΔE in the CIE Lab color space between colors X2 and X3 is less than 10, preferably less than or equal to 8, more preferably less than or equal to 7. Thus, if color X2 is similar to color X1, which is itself similar to color X, there is also a difference ΔE in the CIE Lab color space between colors X and X3 of less than 10, more preferably less than or equal to 8, more preferably less than or equal to 7.

[0047] According to a first variant of the method of the invention, step b) for producing a semi-finished product consists of a method selected from the group comprising 3D printing methods, methods involving exposure to radiation, for example UV or microwave radiation, and combinations thereof.

[0048] According to another variant of the method of the invention, step b) for producing a semi-finished product comprises the following substeps: b1) mixing the gold and metal oxide nanoparticles obtained in step a), preferably Au@silicon oxide or Au@zirconium oxide nanoparticles, with a flowable preceramic polymer, said gold and metal oxide nanoparticles being in solution directly obtained in step a), or in powder form if dried in an intermediate step after step a), or dissolved again if previously dried in powder form, the amount of Au@metal oxide nanoparticles being selected so as to obtain a composite fluid containing at least 18 carats of gold. The flowable preceramic polymer is preferably a fluid, for example having a viscosity of 10-30 cP. Mixing can be carried out using a planetary mixer or by ultrasound. b2) shaping the composite fluid obtained in sub-step b1) so as to form a semi-finished product. b3) carrying out pyrolysis of the composite fluid shaped according to sub-step b2) to obtain a semi-finished product of color X3. Pyrolysis or sintering can be carried out at high temperatures, for example between 1000°C and 1600°C, for example in an inert environment (argon or nitrogen) for a period of 6h to 12h, with a temperature ramp of 10°C / h to 25°C / h.

[0049] The preceramic polymer used during substep b1) is preferably selected from the group comprising polycarbosiloxanes, polycarbosilanes, polysilazanes, polycarbosilazanes, polysilanes and polysilsesquiazanes, which upon pyrolysis form polymer-derived ceramics (PDC), respectively silicon oxycarbide, silicon carbide, silicon nitride, silicon carbonitride and silicon oxynitride. Other preceramic polymers, especially those containing boron, can also be used. The PDC is advantageously selected to be more transparent than gold after pyrolysis, so that light interacts more with gold than with pyrolyzed PDC. Furthermore, when the color X of the gold nanoparticles is black, the PDC is selected to be black after pyrolysis if used alone without the black Au@metal oxide nanoparticles.

[0050] Substep b2) can advantageously be carried out by using a 3D printing method.

[0051] Substep b2) can also consist of a method selected from the group including a method involving exposure to radiation, such as UV or microwave, preferably preceded by ball milling, a casting method, a press molding method and an injection molding method, by using a mold suitable for the part to be produced, for example a PTFE mold, to obtain at the end of substep b2) an unprocessed compact semi-finished product, conventionally called a "green body" in near-net shape, i.e. a product very close to the final shape of the part to be produced. The shaping of the fluid according to substep b2) can in particular be carried out by cold casting, injection pressing or cold extrusion. The shaping of the fluid according to substep b2) can also be carried out by pressing or hot isostatic pressing, by heating the product in its mold at 300 ° C and 60 MPa for 30 minutes. The product is removed from the mold and then optionally heated again at 400 ° C and 60 MPa for 6 hours.

[0052] According to another variant of the method of the invention, step b) for producing a semi-finished product comprises the following substeps: b4) using the solution of gold and metal oxide nanoparticles, preferably Au@silicon oxide or Au@zirconium oxide nanoparticles obtained in step a) to prepare a powder. For this, the Au@metal oxide nanoparticles, preferably Au@silicon oxide or Au@zirconium oxide nanoparticles of the solution obtained in step a) are washed several times with an alcohol, such as ethanol, and then collected by centrifugation. The Au@metal oxide nanoparticles, preferably Au@silicon oxide or Au@zirconium oxide nanoparticles, are then dried, for example in an oven at 60° C., for at least 6 hours, preferably at least 12 hours. b5) mixing said powder obtained according to sub-step b4) with a ceramic so as to obtain a composite powder comprising at least 18 karat gold, the amount of Au@metal oxide nanoparticles being selected so as to obtain a composite powder comprising at least 18 karat gold. b6) forming the composite powder obtained in sub-step b5) so as to form a semi-finished product. b7) carrying out pyrolysis of the composite powder shaped according to substep b6) to obtain a semi-finished product of color X3. The pyrolysis can be carried out as described above for substep b3).

[0053] The ceramic used in substep b5) is preferably selected from the group comprising zirconia, alumina, silicon oxycarbide, silicon carbide, silicon nitride, silicon carbonitride, silicon oxynitride, titanium carbide, titanium nitride, titanium diboride, boron carbide. The ceramic is advantageously selected to be more transparent than gold after pyrolysis, so that light interacts more with the gold than with the pyrolyzed ceramic. Furthermore, when the color X of the gold nanoparticles is black, the ceramic is selected to be black after pyrolysis if used alone without the black Au@metal oxide nanoparticles. The ceramic makes it possible to obtain a composite material comprising at least 18 carat gold, which has very good mechanical properties, improved ductility, hardness and toughness compared to pure gold.

[0054] Substep b6) is advantageously carried out by a conventional method for mounting ceramics, which may consist, for example, of a method selected from the group comprising casting, pressing and injection molding, via the formation of a green body, as described above for substep b2).

[0055] Finally, step c) of producing a watch or jewelry part comprises, for example, a machining and / or finishing process to obtain said watch or jewelry part of color X4, such that the difference ΔE in the CIE Lab color space between colors X3 and X4 is preferably less than 10, preferably less than 8, more preferably less than 7, and the difference ΔE in the CIE Lab color space between colors X2 and X4 is preferably less than 10, preferably less than 8, more preferably less than 7. The machining process is, for example, a milling process or any other suitable method. The mechanical finishing process is, for example, a polishing process or any other suitable method. Thus, if color X2 is similar to color X1, which is itself similar to color X, there is also a difference ΔE in the CIE Lab color space between colors X and X4 of less than 10, preferably less than 8, more preferably less than 7.

[0056] In this way, watch or jewellery parts are obtained from materials including at least 18 carat gold and in particular composite materials of the cermet type combining ceramic and metal, which have all the attractive mechanical properties of ceramics, in particular their ductility, hardness and toughness.

[0057] Nanoparticles comprising a gold core with a silicon or zirconium oxide shell are preferably used, more preferably nanoparticles comprising a gold core with a silica oxide shell.

[0058] A silica or zirconium oxide shell around a gold core has several advantages: - In the case of black gold nanoparticles, the alloy achieves a darker color due to a more effective penetration depth of light, thanks to a better relationship in the refractive index between the metal oxide shell and the gold core. Due to the lower refractive index of silicon dioxide or zirconium dioxide compared to that of titanium dioxide, the interaction of light at the interface between the metal oxide shell and the gold core increases in the solid material. The lower refractive index of silicon dioxide or zirconium dioxide is also an advantage for obtaining 18 carat gold alloys of different colors, e.g. red, blue, purple, and green. - Mechanical properties are improved by using a silicon dioxide or zirconium dioxide shell rather than a titanium dioxide shell due to the increased Vickers hardness. Thus, the overall mechanical strength of the resulting final part is improved and scratch resistance is increased. The lower density of silicon dioxide compared to that of titanium dioxide makes it possible to obtain gold alloys with a higher gold fineness than can be obtained with a titanium dioxide shell.

[0059] Furthermore, the surfactant, in particular PVP, due to its affinity with metal oxides, in particular silica or zirconium, makes it possible to obtain a uniform silica or zirconia shell around the gold nanoparticles. This uniform shell advantageously makes it possible to prevent the fusion of the gold nanoparticles during subsequent heat treatments, such as pyrolysis, so that the plasmonic effect of the gold nanoparticles is preserved and at least the color X2 of the prepared Au@metal oxide nanoparticles is not altered by the different heat treatments necessary to obtain a semi-finished product of color X3, the difference ΔE in the CIE Lab color space between colors X3 and X2 being less than 10, preferably less than 8, more preferably less than 7. Furthermore, the color X2 of the prepared Au@metal oxide nanoparticles is advantageously not altered by the different heat treatments necessary to obtain a watch or jewelry part of color X4, the difference ΔE in the CIE Lab color space between colors X2 and X4 being preferably less than 10, preferably less than 8, more preferably less than 7. If color X2 is similar to color X1 which is itself similar to color X, then the initial plasmonic effect of the gold nanoparticles and the initial color X are preserved, and the difference ΔE in the CIE Lab color space between colors X and X3 is less than 10, more preferably less than 8, more preferably less than 7, and the difference ΔE in the CIE Lab color space between colors X and X4 is preferably less than 10, more preferably less than 8, more preferably less than 7.

[0060] In a particularly preferred method of the present invention, sub-step a1) involves mixing an aqueous solution of a gold precursor (HAuCl4) with an aqueous solution of sodium citrate at an ambient temperature of 25 °C, where the molar ratio of gold / sodium citrate in the solution is 1 / 50 to 1 / 20. The surfactant used in sub-step a2) is polyvinylpyrrolidone (PVP) in an aqueous solution, and the molar ratio of gold / PVP in the solution is 1 / 1 to 3 / 1. The metal oxide precursor used in sub-step a3) is tetraethoxysilane in an alcohol solution. In step a), in the dry powder form, Au@SiO2 nanoparticles having a black color X2 defined in the CIE L*a*b space by the parameters -5 < a* < 5, -5 < b* < 5, and 0 ≤ L* < 10, preferably -1 < a* < 1, -3 < b* < 3, and 0 ≤ L* < 6 are obtained. The semi-finished product obtained in step b) has a color X3 defined in the CIE L*a*b space by the parameters -5 < a* < 5, -5 < b* < 5, and 0 ≤ L* < 15, preferably -1 < a* < 1, -1 < b* < 1, and 0 ≤ L* < 13. The watch or jewelry part obtained in step c) preferably has a color X4 defined in the CIE L*a*b space by the parameters -5 < a* < 5, -5 < b* < 5, and 0 ≤ L* < 15, preferably -1 < a* < 1, -1 < b* < 1, and 0 ≤ L* < 13.

[0061] The present invention also relates to a semi-finished product from a material containing at least 18 karat gold, which is likely to be obtained during the implementation of the method for manufacturing the watch or jewelry part defined above. The semi-finished product has a color defined in the CIE L*a*b space by the parameters -5 < a* < 5, -5 < b* < 5, and L* < 15, preferably -1 < a* < 1, -1 < b* < 1, and L* < 13.

[0062] The present invention also relates to a timepiece or jewelry part obtainable by using a semi-finished product having a color defined in the CIE L*a*b space by the parameters -5 < a* < 5, -5 < b* < 5, and 0 ≤ L* < 15, preferably -1 < a* < 1, -1 < b* < 1, and 0 ≤ L* < 13, which is highly likely to be obtained by the above-described manufacturing method. The timepiece or jewelry part preferably has a color defined in the CIE L*a*b space by the parameters -5 < a* < 5, -5 < b* < 5, and 0 ≤ L* < 15, preferably -1 < a* < 1, -1 < b* < 1, and 0 ≤ L* < 13.

[0063] Such a timepiece or jewelry part is, for example, a vibrating mass, an external element of a watch, or a gemstone.

[0064] The following examples illustrate the present invention but do not limit the scope of the present invention.

Example

[0065] Prepare a citric acid solution (A) containing 54.4 ml of Milli-Q water and 2.72 g of sodium citrate. Prepare a gold solution (B) containing 28 ml of Milli-Q water and 136 mg of HAuCl4·3H2O. Prepare a solution of PVP (C) containing 630 ml of Milli-Q water and 1.55 g of PVP (10K).

[0066] Pour solution A into solution B and continuously stir the reactants for 10 minutes. Then, pour the synthesized black gold colloid into solution C and continuously stir vigorously overnight. Recover the black gold nanoparticles by centrifugation and transfer them to a solution of EtOH and ammonia (6 ml of EtOH + 0.375 ml of ammonia). Immediately dropwise add a solution of TEOS in EtOH (4 ml of EtOH + 0.27 ml of TEOS) and stir vigorously. Stop the reaction after 3 hours. Then, wash the Au@silicon oxide (Au@SiO2) nanoparticles three times with EtOH and finally recover them by centrifugation for drying overnight in a furnace at 60°C.

[0067] The resulting Au@silicon oxide nanoparticles are characterized by transmission electron microscopy (TEM). Figure 3 shows that the resulting Au@silicon oxide nanoparticles are in the form of polymorphous compact reticulated gold coated by a silica shell. The dimensions of the nanoparticles are between 3 and 100 nm, with a silica shell approximately 12 nm thick.

[0068] The Au@SiO2 nanoparticles in the solution obtained in step a) are in powder form, washed several times with ethanol, centrifuged, and then dried in an oven at 60 °C for 12 h.

[0069] The Au@SiO2 nanoparticles in the form of a dry powder have a color X2 defined in the CIE L*a*b space by the parameters a*=0.4, b*=-2.8, L*=5.5, and the measurements are carried out with an X-Rite i1Pro3 instrument. The reflectance of the Au@SiO2 nanoparticles is measured with an X-Rite i1Pro3 instrument for seven samples. By comparison, the reflectance of a black aluminum sheet is measured. The curve illustrated in FIG. 4 is obtained, which corresponds very well to the black Au@SiO2 nanoparticles.

[0070] The Au@SiO2 nanoparticles are then compressed by hot isostatic pressing (HIP) at 300 °C and 667 bar for 1 h. The Au@SiO2 nanoparticles have an intermediate color X' defined in the CIE L*a*b space by parameters a*=0.6, b*=-0.5, L*=13.6. The ΔE in the CIE Lab color space between X2 and X' is 8.4.

[0071] Pyrolysis is then carried out to obtain a semi-finished product containing gold of color X3 of 18 carats, defined in the CIE L*a*b space by parameters a*=0.2, b*=-0.9, L*=12.7. The ΔE in the CIE Lab color space between X3 and X2 is 7.4. The ΔE for the compressed state after HIP is approximately 1 between X3 and X'.

[0072] This indicates that the thermal decomposition of Au@SiO2 nanoparticles does not change the color of the Au@SiO2 nanoparticles obtained during the previous fabrication step. In particular, the color of the synthesized Au@SiO2 nanoparticles is preserved and does not change.

[0073] Furthermore, very black gold nanoparticles and Au@SiO2 nanoparticles are obtained, thus resulting in a component from a composite containing 18 karat gold and ceramic, in which the initial black color of the gold nanoparticles is preserved and unchanged.

Claims

1. 1. A method for manufacturing a watch or jewellery part from a material containing at least 18 carat gold, said method comprising the steps of: a) forming a solution of Au@metal oxide nanoparticles comprising a gold core coated with a metal oxide shell, the step a) comprising at least a1) synthesizing gold nanoparticles by reacting a gold precursor with a reducing agent, said gold nanoparticles having dimensions and shapes that provide a plasmonic effect at least in the visible range; a2) mixing the gold nanoparticles obtained in step a1) with a solution of a surfactant comprising a functional group for coupling to a metal oxide and maintaining stirring for a sufficient time such that the surfactant coats the gold nanoparticles while maintaining the plasmonic effect; a3) forming the metal oxide shell by reacting a metal oxide precursor with the gold nanoparticles obtained in substep a2) while maintaining the plasmonic effect. and b) using the solution obtained in step a) to produce a semi-finished product from a material containing at least 18 carat gold, with the aim of forming said watch or jewellery part while maintaining the plasmonic effect, said semi-finished product obtained has a colour in the dry state such that the difference ΔE in the CIE Lab colour space between the colour of the semi-finished product obtained and the colour of the Au@metal oxide nanoparticles formed in step a) is less than 10, preferably less than 8; c) producing said watch or jewellery part from said material containing at least 18 carat gold using said semi-finished product obtained in step b) while maintaining the plasmonic effect; A method comprising:

2. 2. The process according to claim 1, characterized in that step a) comprises an intermediate sub-step a4) between sub-step a2) and sub-step a3), which comprises the elimination of excess surfactant.

3. The process according to any one of claims 1 to 2, characterized in that the surfactant is selected from the group comprising polyvinylpyrrolidone (PVP), gelatin, silane derivatives and silicate derivatives, preferably polyvinylpyrrolidone (PVP).

4. The method according to any one of claims 1 to 3, characterized in that step b) consists of a method selected from the group comprising 3D printing methods, radiation exposure methods, and combinations thereof.

5. Step b) is b1) mixing the gold and metal oxide nanoparticles obtained in step a) with a flowable preceramic polymer so as to obtain a composite fluid containing at least 18 karat gold; b2) shaping the composite fluid obtained in sub-step b1) to form the semi-finished product; b3) carrying out pyrolysis of the composite fluid formed according to sub-step b2) to obtain the semi-finished product. The method according to any one of claims 1 to 3, comprising:

6. 6. The method of claim 5, wherein the preceramic polymer is selected from the group consisting of polycarbosiloxane, polycarbosilane, polysilazan, polycarbosilazane, polysilane, and polysilsesquiazane to form a polymer-derived ceramic, silicon oxycarbide, silicon carbide, silicon nitride, silicon carbonitride, and silicon oxynitride, respectively.

7. 7. The method according to claim 5, characterized in that substep b2) consists of a method selected from the group comprising 3D printing, radiation exposure, casting, press moulding and injection moulding.

8. Step b) is b4) preparing a powder using the solution of gold and metal oxide nanoparticles obtained in step a); b5) mixing the powder obtained according to sub-step b4) with a ceramic so as to obtain a composite powder containing at least 18 carat gold; b6) forming the composite powder obtained in sub-step b5) to form the semi-finished product; b7) carrying out pyrolysis of the composite powder shaped according to sub-step b6) to obtain the semi-finished product. The method according to any one of claims 1 to 3, comprising:

9. 9. The method of claim 8, wherein the ceramic is selected from the group consisting of zirconia, alumina, silicon oxycarbide, silicon carbide, silicon nitride, silicon carbonitride, silicon oxynitride, titanium carbide, titanium nitride, titanium diboride, boron carbide.

10. 10. The method according to any one of claims 8 and 9, characterized in that sub-step b6) consists of a method selected from the group comprising casting, pressing and injection molding.

11. Method according to any one of the preceding claims, characterized in that step c) comprises a machining and / or finishing treatment to obtain said watch or jewellery part.

12. Method according to any one of the preceding claims, characterized in that the gold nanoparticles obtained in substep a1) have a dimension of less than 200 nm.

13. The reducing agent is NaBH 4 or sodium citrate, preferably sodium citrate.

14. Method according to any one of the preceding claims, characterized in that sub-step a1) comprises mixing the aqueous solution of the gold precursor with an aqueous solution of a reducing agent, at an ambient temperature of 25°C, in which the gold / reducing agent molar ratio in the solution is between 1 / 50 and 1 / 20.

15. The method according to any one of the preceding claims, characterized in that the metal oxide shell has a thickness of less than 100 nm.

16. Method according to any one of the preceding claims, characterized in that the gold precursor is a gold salt, preferably tetrachloroauric acid.

17. The process according to any one of claims 1 to 16, characterized in that the metal oxide precursor is selected from the group comprising tetraethoxysilane for the silica shell, titanium butoxide for the titanium dioxide shell, and zirconium butoxide for the zirconia shell.

18. Sub-step a1) comprises mixing said aqueous solution of gold precursor with an aqueous solution of sodium citrate at an ambient temperature of 25° C., in which the molar ratio of gold / sodium citrate in the solution is between 1 / 50 and 1 / 20, and said gold nanoparticles obtained in sub-step a1) have parameters −5<a*<5, −5<b*<5 and L*<10, preferably Method according to any one of the preceding claims, characterized in that it has a black colour defined in the CIE L*a*b space by -1<a*<1, -3<b*<3 and L*<6.

19. Sub-step a1) comprises determining, in said dry state, said CIE standard deviations according to parameters -5<a*<5, -5<b*<5 and L*<10, preferably -1<a*<1, -3<b*<3 and L*<6 19. Method according to any of the preceding claims, comprising mixing an aqueous solution of gold precursor with an aqueous solution of sodium citrate at an ambient temperature of 25°C, in which the molar ratio of gold / sodium citrate in the solution is between 1 / 50 and 1 / 20, in order to obtain Au@SiO2 nanoparticles having a colour defined in the L*a*b space, characterized in that the surfactant used in sub-step a2) is polyvinylpyrrolidone (PVP) in an aqueous solution, in which the molar ratio of gold / PVP in the solution is between 1 / 1 and 3 / 1, and the metal oxide precursor used in sub-step a3) is tetraethoxysilane in an alcoholic solution, and the colour of the semi-finished product obtained in step b) is defined in the CIE L*a*b space by the parameters -5<a*<5, -5<b*<5 and L*<15, preferably -1<a*<1, -1<b*<1 and L*<13.

20. Semi-finished product from a material containing at least 18 carat gold possibly obtained during the implementation of a method for manufacturing a watch or jewellery part according to any one of claims 1 to 19, characterized in that said semi-finished product has a colour defined in said CIE L*a*b space by the parameters -5<a*<5, -5<b*<5 and L*<15, preferably -1<a*<1, -1<b*<1 and L*<13.

21. A watch or jewellery part possibly obtainable by the manufacturing method according to any one of the preceding claims, characterized in that it is obtained using a semi-finished product having a colour defined in said CIE L*a*b space by the parameters -5<a*<5, -5<b*<5 and L*<15, preferably -1<a*<1, -1<b*<1 and L*<13.

22. 22. A watch or jewellery part according to claim 21, characterized in that it comprises a seismic mass, an external watch element and a jewel.

Citation Information

Patent Citations

  • Pigmented ceramic element

    EP1887052A1

  • Coloured solid precious material made up of an assembly of nanoparticles of noble metals

    EP2369022A1

  • Method of manufacturing a black or anthracite colour material comprising at least 18 gold carats

    EP3482851A1